Assessment of the Allergenic Potential of Trees in the Territory of the Šilutės Vydūnas Gymnasium - Drakšienė, Laura (Jaunųjų mokslininkų darbai, 2025)
Urban green spaces have both positive and negative effects on people’s quality of life. The natural environment has a positive effect on people’s emotional state. People are negatively affected by the pollen emitted by vegetation, which is the main source of airborne allergens. When selecting vegetation for urban green spaces, the allergenicity of plants should be considered. Carinanos et al. (2014) developed an index (IUGZA) to assess the allergenicity of vegetation growing in urban green spaces. The index considers various plant characteristics such as allergenic potential, pollination strategy and duration, number, and size of individuals. The values of the IUGZA index range from 0 to 1, where a value of 0 means that there are no allergenic plants in the area, and a value of 1 means that all plants are allergenic. The area of Šilutė Vydūnas Gymnasium in Lithuania was surveyed 174 trees of different sizes were assessed and the allergenicity index of the area was calculated with a value of 0.046. The value of the index indicates that the site has a low allergenic potential and is therefore considered a favourable environment for people sensitive to inhaled allergens. Although the results of the assessment indicate low allergenicity of the site, it is recommended to increase biodiversity by planting trees and other plants and to ensure proper management and maintenance of urban green spaces.